Productivity and Efficiency of Cashew Processing: Comparison of Manual and Automated Systems - Pai, Ramakrishna; Upadhyaya, Pallavi; Upadhyaya, Y. S. (Prabandhan: Indian Journal of Management, 2019)
India is one of the leading producers, processors, and exporters of cashews in the world. Cashew processing units are primarily small and medium enterprises (SMEs) and are highly labor intensive. Productivity and efficiency of processing is a primary concern for cashew processing firms that operate with limited resources. Using a multiple-case study approach, this study compared the productivity and efficiency of automated cashew processing with the manual processing. Employees’ perception towards automation was also examined. A comparative analysis was performed for the five stages of cashew processing : Sorting, shelling, peeling, grading, and packaging. Purposive sampling method was used to select five SMEs that used either manual or automated processing methods. The study identified the processing method that was the most efficient at each stage, taking into account both quantitative and qualitative data. It was found that automation of the cashew processing increased productivity by at least 10 times. It was also found that almost all the five stages required manual intervention as automation cannot completely replace humans. Due to high health hazards and fatigue, workers favored use of automated processing over manual processing. Health risk was high in the shelling and peeling stages of cashew processing. Fatigue due to repetitive work was high in sorting, grading, and peeling stages. Managerial implications for SME owners who plan to deploy automation technologies in their firms were also discussed.